Renal Pathology in Adult Onset Idiopathic Nephrotic Syndrome A Study of 100 Cases - Tarik, M Hasan; Ekram, ARMS; Haque, Md Azizul; Islam, AKM Monoarul; Uddin, M Jalal (TAJ: Journal of Teachers Association, 2009)
This study was carried out in the nephrology unit to Rajshahi Medical College Hospital, Rajshahi during the period 2003-2005. Renal biopsy was done in one hundred adult patients with Nephrotic syndrome to evaluate the histopathological pattern. Mesangioproliferative GN was the commonest underlying cause which is found in 36 (40%) cases. MPGN is followed by minimal change disease in 22 (24.44%), membranous GN 16 (17.77%), membranoproliferative glomerulonephritis 12 (13.33%), Focal segmental glomerulosclerosis 3 (3.34%) and IgA nephropathy 1 (1.12%) cases. This is concordant with other studies. doi: 10.3329/taj.v20i2.3076 TAJ 2007; 20(2): 140-143